Productivity and Nutrient Quality of Lemna minor as Affected by Microbiome, CO2 Level, and Nutrient Supply - Madeleine C. Zenir; Marina López-Pozo; Stephanie K. Polutchko; Jared J. Stewart; William W. Adams; Adam Escobar; Barbara Demmig-Adams (Stresses, 2022)
Rising atmospheric carbon dioxide (CO2) levels can impact plant photosynthesis and productivity and threaten food security, especially when combined with additional environmental stressors. This study addresses the effects of elevated CO2 in combination with low nutrient supply on Lemna minor (common duckweed). We quantified plant growth rate and nutritional quality (protein content) and evaluated whether any adverse effects of elevated CO2, low nutrients, or the combination of the two could be mitigated by plant-microbe interaction. Plants were grown under controlled conditions and were either uninoculated or inoculated with microorganisms from a local pond that supported L. minor populations. Under low nutrients in combination with high CO2, growth (plant area expansion rate) decreased and biomass accumulation increased, albeit with lower nutritional quality (lower percentage of protein per plant biomass). Inoculation with plant-associated microorganisms restored area expansion rate and further stimulated biomass accumulation while supporting a high protein-to-biomass ratio and, thus, a high nutritional quality. These findings indicate that plant-microbe interaction can support a higher nutritional quality of plant biomass under elevated atmospheric CO2 levels, an important finding for both human and non-human consumers during a time of rapid environmental change.